Proteção laboral e autonomia individual : perspectiva das relações contemporâneas de trabalho - Higa, Felipe Cardoso de Souza (2021)
The conceptions of Labor Law were built aiming to protect workers from the ailments of the capital. The maxim of freedom that guided the Liberal State revealed the unequal exploitation of capital at the expense of human values, demanding greater protection. It was the milestone of the change from the Liberal State to the Welfare State. The transformations in the world of work have limited the capacity of act of the welfare state. From the deductive, dialectical argumentative methods, supported by a literature review of legal, sociological, philosophical and economic science, the concepts of autonomy and protection in the scope of Labor Law are defined. Then, the effectiveness of the protection established by Brazilian Law is analyzed through an economic and statistical analysis. Through the critique of protection, paths are suggested for the realization of the fundamental rights and guarantees of work to new forms of the production process. At last, the conclusions are presented, demonstrating that the protection is based on the vulnerability and low sufficiency of the worker, and the Brazilian State maintains a protective system which demands reforms, aiming at the protection of work, with worker autonomy, through a proposal for reformulation of the fundamental nature of labor rights and the possibility of legitimate negotiation between the parties involved.